Analisis aspek hukum dalam studi kelayakan bisnis: Analisis aspek hukum dalam studi kelayakan bisnis - Radliyah, Diana Rahmah (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the legal aspects in the business feasibility study of Bank Syariah Indonesia (BSI) Malang Kawi Sub-Branch Office (KCP). As part of BSI, KCP Malang Kawi plays a strategic role in supporting the development of Islamic banking in the Malang area. This study includes an analysis of the legality of establishment, license fulfillment, business entity, and ownership profile of BSI. Through a descriptive qualitative approach, this study reveals that the operations of BSI Malang Kawi have fulfilled all legal requirements in accordance with the regulations of the Financial Services Authority (OJK) and sharia principles set by the National Sharia Council (DSN). The results of the analysis show that the existence of BSI Malang Kawi has a solid legal basis, including merger approval, compliance with business entity rules, and close supervision by regulators. This study highlights the importance of a strong legal foundation in supporting the sustainability and competitiveness of sharia-based businesses in Indonesia.